Phytochemicals in olive-leaf extracts and their antiproliferative activity against cancer and endothelial cells - Goulas, Vlasios; Exarchou, Vassiliki; Troganis, Anastassios N.; Psomiadou, Eleni; Fotsis, Theodore; Briasoulis, Evangelos C.; Gerothanassis, Ioannis P. (My University, 2009)
Olive oil compounds is a dynamic research area because Mediterranean diet has been shown to protect against cardiovascular disease and cancer. Olive leaves, an easily available natural material of low cost, share possibly a similar wealth of health benefiting bioactive phytochemicals. In this work, we investigated the antioxidant potency and antiproliferative activity against cancer and endothelial cells of water and methanol olive leaves extracts and analyzed their content in phytochemicals using LC-MS and LC-UV-SPE-NMR hyphenated techniques. Olive-leaf crude extracts were found to inhibit cell proliferation of human breast adenocarcinoma (MCF-7), human urinary bladder carcinoma (T-24) and bovine brain capillary endothelial (BBCE). The dominant compound of the extracts was oleuropein; phenols and flavonoids were also identified. These phytochemicals demonstrated strong antioxidant potency and inhibited cancer and endothelial cell proliferation at low micromolar concentrations, which is significant considering their high abundance in fruits and vegetables. The antiproliferative activity of crude extracts and phytochemicals against the cell lines used in this study is demonstrated for the first time.
Keywords: Angiogenesis; Cancer; LC-SPE-NMR; Oleuropein; Olive leaf extract